How To Plan An Educational Visit To An Historic Site - Sutter, David (Teaching History: A Journal of Methods, 1994)
Teaching history can be far more than dry lectures and reading Jong books. One challenge is to find creative and innovative ways to present the material. Another challenge is to avoid having a visit to an historical site degenerate into an elementary school field trip. The "historical staff ride" program in the United States Army can serve as an example of how to teach history outside of the classroom. The "historical staff ride" is a method for teaching military history by visiting a battlefield and discussing the events that took place. The historic event is then used to teach current Army doctrine. The United States Army has had a leading role in developing this technique.1 Battlefield visits have obvious applications to the education of Army officers. Yet the techniques used in developing a staff ride can be applied to any historical topic. This article provides some ideas on how to develop your own visit to an historical site. For simplicity, this out of classroom event will be called a visitation in this article.